2011
DOI: 10.1002/pc.21172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the resin/hardener ratio on yield, post‐yield, and fracture behavior of nanofilled epoxies

Abstract: In this work, the effect of the resin/hardener ratio on the small deformation, yield, post‐yield, and fracture behavior of a series of DGEBA‐Jeffamine epoxy‐clay nanocomposites with a fixed organo‐clay content (6 phr), and of the corresponding unfilled resins, was investigated. The mechanical behavior at small deformation was studied by means of uniaxial tensile tests, whereas compression tests were employed to investigate the large (yield and post‐yield) deformation levels. The fracture behavior was studied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The molecular architecture of cured epoxies can be modified in different ways, for instance, by changing the chain stiffness of the network, its cross-link density, or its connectivity (Bignotti et al, 2011;Crawford, 1997, 1998;Yang et al, 2007). Several studies have shown that the network architecture greatly affects many properties of epoxy resins, in particular their mechanical properties (Blanco et al, 2009;Crawford, 1997, 1998;Nakka et al, 2011;Pandini et al, 2011;Sindt et al, 1996;Yang et al, 2007) and glass transition temperature (T g ) (Bignotti et al, 2011;Lesser and Crawford, 1998). With regard to the effect of the network architecture on the shape memory behavior of epoxies, the few articles published so far were mainly focused on the tailoring of the switching temperature (Liu et al, 2010;Xie and Rousseau, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular architecture of cured epoxies can be modified in different ways, for instance, by changing the chain stiffness of the network, its cross-link density, or its connectivity (Bignotti et al, 2011;Crawford, 1997, 1998;Yang et al, 2007). Several studies have shown that the network architecture greatly affects many properties of epoxy resins, in particular their mechanical properties (Blanco et al, 2009;Crawford, 1997, 1998;Nakka et al, 2011;Pandini et al, 2011;Sindt et al, 1996;Yang et al, 2007) and glass transition temperature (T g ) (Bignotti et al, 2011;Lesser and Crawford, 1998). With regard to the effect of the network architecture on the shape memory behavior of epoxies, the few articles published so far were mainly focused on the tailoring of the switching temperature (Liu et al, 2010;Xie and Rousseau, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The stoiciometric formulation 13 phr is showing better elongation than the 10 phr, that's due to the amino addition reaction which is the dominated, that makes the material more flexible and ductile so that it would withstand the applied load. The 20 phr is showing less elongation than the 15 phr, that's due to the non reacted hardener molecules which makes the material brittle [18].…”
Section: Effect On the Ultimate Tensile Strengthmentioning
confidence: 97%
“…al. [18] and Lee [19] where they found that the Young's modulus increase with the increase of the hardener/resin ratio. The Young's modulus for the DGEBA/DDM system is higher than that for the DGEBA/TETA system; this is due to the aromatic structure in the backbone which imparts better rigidity to the epoxy resin system making the material more stable and showing higher resistance to the pulling load [20].…”
Section: Effect On the Elastic Modulusmentioning
confidence: 99%
“…Epoxy resins are usually prepared through crosslinking of epoxy oligomers with active-hydrogen compounds, such as anhydrides and aromatic or aliphatic polyamines, termed as hardeners. A proper formulation of the reaction mixture, through the variation of as the stoichiometric ratio [1][2][3][4][5][6][7][8][9][10], the type of resin and hardener [2,[11][12][13], the use of chains extenders [13] or blends of different monomers [7,8,15], allows to significantly vary the chemical and physical properties of the resins. In particular, their mechanical response at small and large strains [15], their thermomechanical behavior [2], and their fracture resistance [17][18][19][20] may be significantly influenced by parameters related to the specific resin formulation, such as the choice of specific hardener-to-resin ratios, which is perhaps the easiest way to vary the mechanical response of epoxy resins and epoxy-based particulate composites [1, 6-8, 20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the postyield strain softening and hardening behavior is seen to be mainly ruled by the crosslink density [27], and a further contribution may be provided by physical crosslinking, as that ascribed to hydrogen bonding between the network segments and the antiplasticizers [31]. It is anyway important to remark that in presence of complex formulations, such as those achieved by changing the resin/hardener ratio, where segmental chain mobility and crosslink density are simultaneously varied, the behavior at yield and postyield is governed by a combination of these effects which cannot be separated [6].…”
Section: Introductionmentioning
confidence: 99%